Prognostic significance of modern markers of severity and development of complications in acute cerebrovascular diseases - Gozhenko, A. I.; Kovalevska, L. A.; Telyatnikov, O. V. (Journal of Education, Health and Sport, 2018)
Recent studies have shown significantly increasing importance of new risk factors such as high levels of homocysteine and C-reactive protein, the presence of thrombophilia markers in the development of stroke. However, information of their relationship in acute defferent types of stroke and acute cardio-vasculares complications caused by stroke, is limited. The study showed that the impact of biomarkers on the stroke severity is age-dependent and hyperhomocysteinemia is play great importance role.